High recruitment associated with increased sea temperatures towards the southern range edge of a Western Australian endemic reef fish Choerodon rubescens (family Labridae) - Cure, K.; Hobbs, Jean-Paul; Harvey, Euan (Springer, 2015)
Choerodon rubescens is a subtropical wrasse endemic to Western Australia which has recently recruited in high abundance into lagoonal habitats at the southern end of its distribution. Abundance, size structure and habitat associations of juvenile C. rubescens were assessed during summer and autumn 2013 (January–May) via underwater visual census across available shallow water habitats towards the southern range edge of their distribution (32°S, 115°E). High abundances of juveniles (up to 14 fish/40 m2) were found in areas where they were previously absent or in low abundance. Lagoonal habitats presented abundances three to eight times higher than seagrass beds or rocky reef, indicating preference of C. rubescens for mixed lagoonal habitatsas settlement grounds. Such habitats contain open sandy areas with small rocks and rubble that are important feeding grounds for juveniles. Based on the size structure of populations encountered, recruitment was estimated to occur during summer 2011–12 and 2012–13.This coincides with water temperatures 1 to 2 °C higher than long-term averages in the region, making conditions more favourable for recruits to survive in greater numbers. We conclude that the high abundance of C. rubescens recruits towards the southern end of their distribution together with trends of increasing water temperature and the availability of suitable settlement habitat to the south of their present range, indicate a capacity for the species to shift its distribution southwards.Monitoring of future recruitment events will be crucial to determining range expansion capacity andguiding management efforts for this endemic and important fisheries species.